Penerapan Informed Consent di Klinik Pratama Tiara Husada - Tjokorda Istri Agung Devitia Widya Paramita Putri; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Interpretasi Hukum, 2022)
The aim is to implement informed consent at Tiara Husada Primary Clinic. This research includes empirical legal research based on sociological, factual, and conceptual approaches. The data is sourced from the results of field research and legislation. While the data collection is done by using the technique of documentation, interviews and literature research. The results of the research show that the implementation of the approval of medical actions at the Tiara Husada Pratama Clinic is juridically in accordance with applicable regulations, where in its implementation it is prioritized on the communication process between doctors and their patients, not only on filling out and signing forms. If there is a difference of opinion between the doctor and his patient regarding the medical action to be carried out, the medical personnel in the settlement, will continue to try to respect the patient's human rights by continuing to provide the best service, providing other alternative actions even though the results are not optimal compared to the medical actions that have been suggested, and didn't force them to go home.